Domestic and International Price-setting Mixed Triopolies - Ferreira, Fernanda A.; Ferreira, Flávio (Journal of Applied Nonlinear Dynamics, 2026)
We will consider two models describing certain market structures: (i) a domestic market in which a public firm (whose objective is to maximize social welfare) competes with two private firms (whose objective is to maximize their own profits); and (ii) an international market in which a domestic public firm competes with one domestic private firm and one foreign private firm. In both situations, firms decide simultaneously the price for their substitutable goods. We compare the maximum-revenue tariff with the optimum-welfare tariff, and also the other output equilibria obtained in each case. Furthermore, we also compare the results in the domestic competition with the ones in the international competition.